Laporan PPM/Monash University Library: staff development and training program - Ali, Rugayah (Persatuan Pustakawan Malaysia, 2008)
The Persatuan Pustakawan Malaysia (PPM is continuously trying to improve the knowledge and skills of Malaysian librarians. One such effort is through the Staff Development and Training Programme which was made possible with the heh: of the Monash University Library. This article describes the programme which was conducted from 7 to 27 Julv 2004.